A simple formula to fabricate high performance lithium metal capacitors - NurulHuda, Shah; Ling, JinKiong; Ghufira, .; Izan Izwan, Misnon; Wu, Yi-Shiuan; Yang, Chun-Chen; Jose, Rajan (Elsevier Ltd, 2024)
Energy storage technologies that are low-cost, with long cyclability, high rate-capability as well as high energy and power densities are under intensive investigation for sustainable clean energy transition. In this paper, we report a high-performance lithium metal capacitor (LMC) achieved by a simple slurry modification during the cathode film preparation. We show that a mere substitution of ~0.4 wt% conductive carbon by single walled carbon nanotubes (SWCNTs) increased the specific energy of LMCs by 22 %. Porous carbon cathode in this study was obtained from a non-edible biomass (coconut rachis); the optimized sample showed desirable surface characteristics (surface area ~1933 m2⸱g−1 and pore diameter ~2.0 nm) as well as high edge-plane fraction (ratio between relative density of edge and basal plane ~0.4). Cathode with no SWCNTs show a specific capacitance (CS) of ~133 F·g−1@0.1 A·g−1 in the potential window 2.0–4.0 V in the Li//LiPF6//AC device configuration. Removal of conductive carbon by SWCNTs up to ~0.6 wt% increased electrical conductivity of the cathode; however, the charge storability enhancements were only up to ~0.4 wt%. The optimum device delivered a CS ~188 F·g−1@100 mA·g−1 in the potential window 2.0–4.0 V with improved rate capability and cycling stability. Electrochemical impedance spectroscopy was used as a tool to understand the charge kinetics at the electrode; these studies collectively validated the observed enhancements in the charge storability. The device hereby developed showed superior specific capacity than most of the reported lithium-ion capacitors and comparable to some of the LMBs. The perceived 22 % increase in the specific energy by a mere 0.4 wt% SWCNT substitution is a step forward in fabricating the high-performance LMCs in addition to support the sustainability agenda through the carbon-negative precursors.